2003
DOI: 10.1097/01.wcb.0000071883.63724.a7
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Glial Reactivity to Stroke in Aged Rats Correlates with Reduced Functional Recovery

Abstract: Following cerebral ischemia, perilesional astrocytes and activated microglia form a glial scar that hinders the genesis of new axons and blood vessels in the infarcted region. Since glial reactivity is chronically augmented in the normal aging brain, the authors hypothesized that postischemic gliosis would be temporally abnormal in aged rats compared to young rats. Focal cerebral ischemia was produced by reversible occlusion of the right middle cerebral artery in 3- and 20-month-old male Sprague Dawley rats. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
178
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(202 citation statements)
references
References 46 publications
20
178
2
Order By: Relevance
“…Aged rats with ischemic insult were shown to develop larger infarct volumes [39][40][41] or greater tissue distortion than young animals [28]. These observations might be related to increased necrosis, damaged blood-brain barrier, and enhanced microglial activation that were reported for aged animals [39][40][41][42].…”
Section: Discussionmentioning
confidence: 81%
“…Aged rats with ischemic insult were shown to develop larger infarct volumes [39][40][41] or greater tissue distortion than young animals [28]. These observations might be related to increased necrosis, damaged blood-brain barrier, and enhanced microglial activation that were reported for aged animals [39][40][41][42].…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, it has been reported that aged rats have accelerated glial reactivity in response to cerebral ischemia, which coincides with stagnation of functional recovery. 25 Thus, the worsening of neurological deficits in Tg huS100B mice after pMCAO may represent an event caused by inappropriately accelerated glial responses.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, experimental studies of radiation-induced inflammation, brain injury and cognitive dysfunction have been conducted almost exclusively in animals a few weeks to a few months old, young ages that do not reflect important neurobiological changes that occur with normal aging, such as decreased proliferation and neurogenesis (15)(16)(17)(18), increased microglial activation (19,20) and expression of pro-inflammatory cytokines (20)(21)(22). Experimental studies of stroke, traumatic brain injury, exogenous cytokine administration, and axotomy support the hypothesis that aging impacts the intensity and duration of brain inflammation and glial activation following challenges (23)(24)(25)(26)(27)(28). Moreover, evidence that old age impacts the duration of some radiation-induced cognitive deficits in rodents (29,30) suggests greater radiation-induced injury in older rats.…”
Section: Introductionmentioning
confidence: 99%